Strokovna terminologija - gradnik interoperabilnosti kulturnih in z njimi povezanih vsebin - Novak, Miroslav (Knjižnica, 2011)
The author defines the term "interoperability" as the ability of information system to interexchange data, information and knowledge. These processes can take place within a field or among different professional areas. One of the preliminary conditions for successful communication based on consistent professional terminology. The author exposes some basic archival professional terms defined in the current Slovenian archival legislation and professional standards. He stresses some semantic problems of implementation of these terms in different fields. In his opinion terminological deficiencies must be coordinated if we want to achieve long-term sustainability and usability of the cultural contents in the electronic environment. Otherwise these problems can represent a serious threat of the expected interoperability realization.
Keywords: arhivistika; archival science; arhivi; arhivsko gradivo; terminologija; terminology; digitalizacija; digitization; digitalni viri